Optimalisasi Kemampuan Guru Dalam Implementasi Kurikulum Merdeka di SMA Negeri 1 Dolok Batu Nanggar Kabupaten Simalungun - Hutahaean, Berman; Gultom, Candra Ronitua; Silitonga, Parasian D.P.; Ginting, Dicky Alpredo; br. Tarigan, Monica Marcelina; Sihite, Jernyta; Lasmarito Saruksuk, Hotti Sanogaria (STMIK Royal, 2025)
The main problem faced by SMA Negeri 1 Dolok Batu Nanggar in implementing the Independent Curriculum is the readiness and competence of teachers in implementing innovative learning methodologies that are in accordance with the demands of the curriculum. This community service activity aims to improve teacher competence, strengthen learning infrastructure, and support school readiness in implementing the Independent Curriculum in the school. The implementation of this activity consists of several stages: socialization, training, technology procurement, mentoring, and periodic evaluation. Socialization introduces the essence of the Independent Curriculum and the role of teachers in its implementation. Intensive training is provided regarding innovative learning methods, including flipped classrooms and project-based learning. The procurement of technological devices such as CCTV, digital library applications, and laptop speakers aims to support an interactive and modern learning environment. Mentoring is also carried out in the preparation of teaching modules that are relevant to the new curriculum. The results of the activity show an increase in teacher competence in implementing innovative learning methods and strengthening technological infrastructure in schools. This activity emphasizes the importance of ongoing training and monitoring to ensure effective and sustainable curriculum implementation.Keywords: Merdeka Curriculum; teacher training; learning innovation; learning technology; project-based learning. Abstrak: Permasalahan utama yang dihadapi oleh SMA Negeri 1 Dolok Batu Nanggar dalam implementasi Kurikulum Merdeka adalah kesiapan dan kompetensi guru dalam menerapkan metodologi pembelajaran yang inovatif dan sesuai dengan tuntutan kurikulum tersebut. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru, memperkuat infrastruktur pembelajaran, dan mendukung kesiapan sekolah dalam mengimplementasikan Kurikulum Merdeka di sekolah tersebut. Pelaksanaan kegiatan ini terdiri dari beberapa tahap: sosialisasi, pelatihan, pengadaan teknologi, pendampingan, dan evaluasi berkala. Sosialisasi memperkenalkan esensi Kurikulum Merdeka dan peran guru dalam penerapannya. Pelatihan intensif diberikan terkait metode pembelajaran inovatif, termasuk flipped classroom dan pembelajaran berbasis proyek. Pengadaan perangkat teknologi seperti CCTV, aplikasi perpustakaan digital, dan pengeras suara laptop bertujuan mendukung lingkungan belajar yang interaktif dan modern. Pendampingan juga dilakukan dalam penyusunan modul ajar yang relevan dengan kurikulum baru. Hasil kegiatan menunjukkan peningkatan kompetensi guru dalam menerapkan metode pembelajaran inovatif dan penguatan infrastruktur teknologi di sekolah. Kegiatan ini menegaskan pentingnya pelatihan berkelanjutan dan pemantauan untuk memastikan penerapan kurikulum yang efektif dan berkesinambungan.Kata Kunci: Kurikulum Merdeka; pelatihan guru; inovasi pendidikan; teknologi pendidikan; pembelajaran berbasis proyek.